Justification of the choice of composite material for the restoration of teeth after endodontic treatment - A. V. Mitronin; D. Yu. Fadeeva; T. V. Grineva; V. N. Chilikin (LLC "Endo Press", 2020)
Relevance. The forecast of the functionality of the tooth after endodontic treatment, when resistance to mechanical loads is significantly reduced, depends on the choice of method and material for the restoration.Aim. The aim of the work was to compare the physicomechanical and clinical qualities of composite materials used to restore posterior teeth after endodontic treatment.Materials and methods. Studies were carried out according to GOST 31574-2012 - determination of the curing depth, strength with diametral rupture, bending and determination of water absorption and water solubility, as well as the integrity of the restorations, the presence of chips, the development of secondary caries after 24 months.Result of research. Based on a comparison of the physicomechanical and clinical qualities of the composite materials Tetric EvoCeram (Ivoclar Vivadent) and SDR (Dentsply) used to restore the posterior teeth after endodontic treatment, as well as the timing of the time spent on treatment, the choice of a composite material for the restoration is justified.Conclusions. Indicators for all the parameters studied composite materials Tetric EvoCeram and SDR more perfect than required by GOST. The time spent on the restoration of the posterior teeth using a two-layer technique using the composite SDR as the basis and restoring the occlusal surface with the Tetric EvoCeram composite is significantly on average 10 minutes less than with a tooth restoration using the multilayer Tetric EvoCeram composite material ( p ≤ 0.05).